OPTIMALISASI FEED INSTAGRAM SEBAGAI MEDIA DAKWAH: STUDI KASUS AKUN @QURANREVIEW DALAM MENINGKATKAN PEMAHAMAN AL-QUR’AN MELALUI PLATFORM BROADCASTING DIGITAL - Famuji, Untung; Khotimah, Khusnul (Fakultas Komunikasi dan Desain Program Studi Komunikasi dan Penyiaran Islam, 2025)
This study aims to analyze the optimization of Instagram feed as a medium for da’wah to enhance the understanding of the Qur’an, with a case study on the Instagram account @quranreview. In the digital era, the use of social media as a platform for da’wah has become increasingly relevant, especially for reaching the younger generation. The research employed a qualitative approach with a case study method, collecting data through interviews, observations, and documentation. The key findings indicate that @quranreview optimizes its Instagram feed through engaging visual design, the application of social influence principles such as reciprocity and social proof, and active interaction with the audience to deepen Qur’anic understanding. The practical implications of this research emphasize the importance for digital da’wah account managers to effectively utilize visual elements and audience interaction in conveying relevant and engaging religious messages. This research also contributes theoretically to the development of digital da’wah understanding through social media.